2009
DOI: 10.1148/rg.292085123
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging of Hypervascular Liver Masses: A Review of Current Techniques

Abstract: Major technologic advances in magnetic resonance (MR) imaging, including the advent of novel pulse sequences (eg, diffusion-weighted and steady-state free precession sequences) and the use of hepatocyte-specific contrast agents, have led to better image quality and shorter acquisition times, resulting in dramatic improvements in the noninvasive detection and characterization of hepatic lesions, particularly hypervascular neoplasms. However, as the role of MR imaging in clinical evaluation of the liver continue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(68 citation statements)
references
References 61 publications
(68 reference statements)
5
60
0
3
Order By: Relevance
“…Hepatic hemangiomas, usually solitary, are well-circumscribed lesions containing blood-filled spaces lined by endothelium on a thin fibrous stroma [15]. Occasionally, giant hemangiomas (>4-6 cm) may cause nonspecific abdominal symptoms related to mass effect [16]. In two-thirds of the cases, hemangiomas appear as homogenously hyperechoic masses on US [17].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatic hemangiomas, usually solitary, are well-circumscribed lesions containing blood-filled spaces lined by endothelium on a thin fibrous stroma [15]. Occasionally, giant hemangiomas (>4-6 cm) may cause nonspecific abdominal symptoms related to mass effect [16]. In two-thirds of the cases, hemangiomas appear as homogenously hyperechoic masses on US [17].…”
Section: Methodsmentioning
confidence: 99%
“…On contrast-enhanced US, CT or MRI, hemangiomas may demonstrate either a characteristic pattern of peripheral nodular discontinuous enhancement that progresses centripetally to uniform enhancement, or immediate uniform enhancement which follows the blood pool on subsequent phases, termed “flash-filling hemangioma” (Fig. 2) [16]. On T2-weighted MRI, hemangiomas tend to have a markedly hyperintense appearance, also called “light bulb bright” appearance.…”
Section: Methodsmentioning
confidence: 99%
“…The other 10 patients had normal background liver, but four of the 10 patients had a total of 15 metastatic liver tumors originating from a gastrointestinal stromal tumor (n = 9), rectal cancer (n = 5), or renal cell carcinoma (n = one). The HCCs and metastatic liver tumors were diagnosed using validated imaging criteria, 3,4,[15][16][17][18] elevated tumor markers (e.g., ¡-fetoprotein and des-£-carboxy prothrombin for HCC, carcinoembryonic antigen, or carbohydrate antigen 19-9 for metastatic liver tumor) and follow-up imaging studies performed at least 6 months after the DWI, which showed tumor shrinkage with treatment or tumor progression without treatment.…”
Section: Clinical Study Patientsmentioning
confidence: 99%
“…DWI provides functional information, such as that of the motion or diffusion of water molecules, and can be used to detect and characterize malignant and nonmalignant lesions. [1][2][3][4][5][6][7] However, DWI suffers from low spatial resolution because it must maintain a usable signal-to-noise ratio (SNR) compared to conventional T 2 -weighted imaging. 8 In addition, DWI is generally scanned using an echo planar imaging (EPI) technique, which occasionally yields artifacts, such as ghosting, distortion, and chemical shift artifacts.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional T2-or T1-weighted MRI highlight anatomical changes to characterize hepatic nodules within a cirrhotic background [10,11]. MR angiography using gadolinium agent contrast enhancement (CE) is a clinical imaging standard tool for evaluating and detection HCC based on blood supply and vascular integrity.…”
Section: List Of Figuresmentioning
confidence: 99%